Cycling in the Absence of Task-Related Feedback: Effects on Pacing and Performance - Smits, Benjamin L. M.; Polman, Remco C. J.; Otten, Bert; Pepping, Gert-Jan; Hettinga, Florentina J. (Frontiers in Physiology, 2016)
Introduction. To achieve personal goals in exercise task completion, exercisers have to regulate, distribute and manage their effort. In endurance sports, it has become very commonplace for athletes to consult task-related feedback on external devices to do so. The aim of the present study was to explore the importance of the presence of this information by examining the influence of the absence of commonly available task-related feedback on effort distribution and performance in experienced endurance athletes. Methods. A 20-km cycling time trial was performed. 20 Participants from a homogenous cyclist population were appointed to a group that did not receive any feedback (NoF), or a group that could consult task-related feedback (i.e., speed, heart rate, power output, cadence, elapsed time and elapsed distance) continuously during their trial (FF). Results. The distribution of power output (PO) differed between groups. Most evident is the spurt at the end of the trial of FF, which was not incorporated by NoF. Nevertheless, no between-group differences were found in performance time (FF: 28.86 +/- 3.68 min vs. NoF: 30.95 +/- 2.77 min) and mean PO controlled by body mass (FF: 3.61 +/- .60 W/kg vs. NoF: 3.43 +/- .38 W/kg). Also, no differences in rating of perceived exertion scores were found. Conclusion. The current study provides a first indication that prior knowledge of task demands together with reliance on bodily and environmental information can be sufficient for experienced athletes to come to comparable time trial performances. This questions the necessity of the presence of in-race instantaneous task-related feedback via external devices for maximising performance. Moreover, it seems that different pacing strategies emerge depending on sources of information available to experienced athletes.